Effect of arbuscular mycorrhizal fungi on nutrients and heavy metals uptake by Pennisetum purpureum cv Mott in phytoremediation of gold mine tailings - Bela Putra; Lili Warly; Evitayani Evitayani; Bopalion Pedi Utama (Brawijaya University, 2022)
Mercury composite and cyanidation are gold mining methods that are frequently used. The mercury composite method produces tailings containing heavy metals that can harm living organisms. Utilisation of tailings for the development of forage may be enhanced through arbuscular mycorrhizal fungi (AMF) inoculation to increase plant resistance, absorption of macro and micronutrients, and reduce levels of metal contaminants in the tailings. This study aimed to investigate the effect of arbuscular mycorrhizal fungi on nutrients and heavy metals uptake by Pennisetum purpureum cv Mott in phytoremediation of gold mine tailings. Treatments consisted of four levels of AMF inoculation (0, 5, 10 and 15 g pot-1) were arranged in a completely randomised design with five replications. Each pot contained 3 kg of tailings. The results showed that the best crude protein, crude fiber, crude fat, Ca, and P contents in the plant shoots was obtained by providing AMF inoculation of 15 g pot-1. However, the treatment had no significant effect on dry weight, dry matter, and nitrogen-free extract. AMF significantly increased the uptake of heavy metals by the plant roots. The treatments did not significantly affect Pb uptake by plant roots and shoots and Hg uptake by plant shoots. AMF treatments significantly reduced the translocation factor (TF) value for Hg, bioconcentration factor (BCF) values for Cd and Pb, and removal efficiency (RE) values for Cd and Pb. AMF could effectively increase nutrient absorption in the plant shoots, reduce Cd, Hg, and Pb translocation in plant shoots, and reduce Cd, Hg, and Pb in the tailings.